Usage of Rotary Instruments in Root Canal Therapy of Deciduous Teeth - Review - Pınar Demir; İnci Kırmızıgül (Cumhuriyet University, 2019)
Maintaining the deciduous teeth in the mouth until the time of physiological exfoliation is of great importance for the health of the permanent dentition. Root canal treatment, also called pulpectomy, performed in cases of inflammation or necrosis of the deciduous teeth pulp, is indicated as a successful method to preserve the tooth functionally. Conventional pulpectomy procedure is performed with stainless steel files, however, the low elasticity of these files may cause undesirable canal shapes and the time-taking treatment period may lead to deterioration of the patient's cooperation, especially in pedodontics. Ni-Ti rotary instrument systems eliminate these disadvantages and provide better quality canal fillings in a shorter duration. The present article reviewed the studies that are comparing the traditional stainless steel files and Ni-Ti rotating instrument for the root canal treatment of deciduous teeth.